The world of textbooks - the experience of a historical textbook research - Molnár-Kovács, Zsófia (Autonomy and Responsibility Journal of Educational Sciences, 2022)
Introduction: I often ask myself: why do I do research, why do I like to do research? Why, moreover, am I interested in textbooks, their research possibilities, their historical sources, their bibliographical background, their bibliographical collection? What motivates me? What keeps me going?...